SOCIALIZATION AND IMPLEMENTATION OF LONG RANGE IN MONITORING PLANT CONDITIONS IN GREENHOUSES IN PALEMBANG CITY - Salamah, Irma; Suzanzefi, Suzanzefi; Ningrum, Shinta Sulistiya; Kusmanto, RD. (UNIVERSITAS PGRI MADIUN, 2024)
Abstract. Palembang City is an area that has several ornamental plant farmers with quite ample sales opportunities. However, the influence of the unfavourable environment has disrupted the process of cultivating several plants with high selling prices. Therefore, this community service activity aims to examine the long-term application of technology in monitoring the condition of plants in greenhouses. The tools used in this extension enable more extensive, accurate and efficient monitoring of temperature and humidity in the greenhouse. The target of this activity is an effort to support the results of practical work on making tools that are useful for farmers or ornamental plant hobbyists. Implementation will be carried out from January to August 2023. The initial stage is to submit proposals and reports to ornamental plant farmer business partners, which will be reviewed directly together. Then, preparations are made for making tools that suit the farmers' basic needs, and then the first partner, who will be the focal point for the tools to deliver the material, is selected, as well as how to use and hand over the equipment. The result of this activity is that farmers can demonstrate an increased understanding of long-term benefits and their role in optimizing greenhouse management. This successful implementation underscores Long Range's potential to revolutionize greenhouse farming. Overall, teaching and practical experience play an essential role in facilitating the use of advanced technologies, ultimately improving agricultural practices and outcomes. This also highlights the importance of obtaining information and knowledge related to the application of IoT technology, which is very beneficial for everyday life. Abstrak. Kota Palembang merupakan daerah yang memiliki beberapa petani tanaman hias dengan peluang penjualan yang cukup luas. Namun pengaruh lingkungan yang kurang mendukung mengganggu proses budidaya beberapa tanaman yang harga jualnya tinggi. Oleh karena itu, kegiatan pengabdian masyarakat ini bertujuan untuk mengkaji penerapan teknologi jangka panjang dalam pemantauan kondisi tanaman di rumah kaca. Alat yang digunakan dalam ekstensi ini memungkinkan pemantauan suhu dan kelembapan di rumah kaca secara lebih ekstensif, akurat dan efisien. Sasaran kegiatan ini adalah upaya menunjang hasil kerja praktek pembuatan alat-alat yang berguna bagi petani atau penghobi tanaman hias. Pelaksanaannya akan dilakukan pada bulan Januari hingga Agustus 2023. Tahap awal adalah penyampaian proposal dan laporan kepada mitra usaha petani tanaman hias untuk dikaji langsung bersama. Kemudian dilakukan persiapan pembuatan alat yang sesuai dengan kebutuhan dasar petani, kemudian dipilih mitra pertama yang akan menjadi fokal alat untuk menyampaikan bahan, serta cara penggunaan dan penyerahan alat tersebut. . Hasil dari kegiatan ini adalah para petani dapat menunjukkan peningkatan pemahaman mengenai manfaat jangka panjang dan peran mereka dalam mengoptimalkan pengelolaan rumah kaca. Keberhasilan implementasi ini menggarisbawahi potensi Long Range untuk merevolusi pertanian rumah kaca. Secara keseluruhan, pengajaran dan pengalaman praktis memainkan peran penting dalam memfasilitasi penggunaan teknologi maju, yang pada akhirnya meningkatkan praktik dan hasil pertanian. Hal ini sekaligus menyoroti pentingnya memperoleh informasi dan pengetahuan terkait penerapan teknologi IoT yang sangat bermanfaat bagi kehidupan sehari-hari.